Income Inequality And Economic Segregation In Indonesian Crime Patterns: Ketimpangan Pendapatan Dan Segregasi Ekonomi Terhadap Kejahatan Di Indonesia - Anna Khairunnissa; Ratu Eva Febriani (Academia Open, 2026)
General Background: Crime remains a persistent socio-economic challenge in Indonesia, closely associated with disparities in welfare and regional development. Specific Background: Previous studies emphasize income inequality, poverty, education, and unemployment as crime-related factors, yet spatial economic separation has received limited empirical attention within the Indonesian context. Knowledge Gap: Empirical evidence simultaneously examining income inequality and economic segregation over a long provincial panel period in Indonesia remains scarce. Aims: This study examines the relationships between income inequality, economic segregation, and crime rates in Indonesia, while controlling for poverty, education, and unemployment. Results: Using panel data from 34 provinces during 2013–2023 and a Fixed Effects Model with EGLS estimation, the findings indicate that income inequality and poverty are positively associated with crime, while education, unemployment, and economic segregation show negative associations. Economic segregation demonstrates a statistically significant negative relationship with crime, suggesting the presence of social cohesion and informal control mechanisms in economically homogeneous communities. Novelty: The study introduces economic segregation measured by an isolation index within a long-term cross-provincial panel framework, offering contextual evidence from Indonesia. Implications: These results suggest that crime mitigation strategies should not rely solely on income redistribution but also consider spatial economic structures, education development, and community-based social cohesion within inclusive regional planning. Highlights • Income inequality and poverty are positively associated with crime rates across Indonesian provinces.• Economic segregation shows a negative association with crime in economically homogeneous communities.• Education and unemployment patterns reflect the role of informal social control mechanisms. Keywords Crime Rate; Income Inequality; Economic Segregation; Social Cohesion; Indonesia